2018
DOI: 10.1287/ited.2017.0178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supplemental Instruction on Business Courses: A Statistical Study

Abstract: Abstract. Many students in quantitative business courses are struggling. One technique designed to support such students is Supplemental Instruction (SI), which is most popular in the science, technology, engineering, and mathematics (STEM) disciplines. In this paper, we show the positive impact of SI on student performance in two bottleneck business courses in a large university. Our evaluation results establish that (i) SI has a statistically significant effect on students' likelihood of passing both courses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Partial correlations (controlling again for Math ACT) calculated when splitting the sample in half by the median course score resulted in a weak positive correlation for low performing students between minutes viewed and average quiz scores (r = .17, p < .05). This is consistent with several studies that found higher grades for low-achieving students who made use some form of supplemental instruction (Lach & Danner, 2013;Mitra & Goldstein, 2018;Owston et al, 2011;Sargent et al, 2013).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Partial correlations (controlling again for Math ACT) calculated when splitting the sample in half by the median course score resulted in a weak positive correlation for low performing students between minutes viewed and average quiz scores (r = .17, p < .05). This is consistent with several studies that found higher grades for low-achieving students who made use some form of supplemental instruction (Lach & Danner, 2013;Mitra & Goldstein, 2018;Owston et al, 2011;Sargent et al, 2013).…”
Section: Resultssupporting
confidence: 92%
“…However, neither group demonstrated a correlation between minutes viewed and course grade. This mixed finding is consistent with other research about supplemental and supplemental video instruction, where some found significant positive effects on student performance as a result (e.g., Green et al, 2012;Hibbert, 2014;Lloyd & Robertson, 2012;Loch et al, 2014;Mitra & Goldstein, 2018;Morris & Chikwa, 2014) and others did not (e.g., Halupa & Caldwell, 2015;Love et al, 2014).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations